2021
DOI: 10.1111/pbr.12981
|View full text |Cite
|
Sign up to set email alerts
|

Features of transcriptional dynamics of the duplicated Vernalization‐B1 gene in wheat (Triticum spp.)

Abstract: The Vernalization‐1 genes are the key determinants of the vernalization requirement of wheat. In the present study, for the first time, the characteristics of VRN‐B1 expression were investigated in accessions of winter hexaploid wheat of Triticum spelta, carrying one and two copies of this gene per haploid genome. Expression of duplicated VRN‐B1 was analysed relative to the single copy allele during vernalization and following vegetative growth. Furthermore, the effect of vernalization duration on transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This is in agreement with the study of Würschum et al (2015) and Dixon et al (2019) who did not find an effect of VRN-A1 CNV on flowering time. Díaz et al (2012); Dixon et al (2019) , and Muterko and Salina (2021) showed an effect of CNV on vernalization requirement. We found strong correlations with six other agronomic traits.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is in agreement with the study of Würschum et al (2015) and Dixon et al (2019) who did not find an effect of VRN-A1 CNV on flowering time. Díaz et al (2012); Dixon et al (2019) , and Muterko and Salina (2021) showed an effect of CNV on vernalization requirement. We found strong correlations with six other agronomic traits.…”
Section: Discussionmentioning
confidence: 95%
“…This gene is considered to be a copy of the Vrn-A1 gene on chromosome 5A. Recently, copy numbers for the dominant alleles of VRN-A1 and recessive allele of VRN-B1 have been detected in different species of wheat by Muterko and Salina, 2018 , 2019 , 2021 and Strejčková et al (2021) .…”
Section: Introductionmentioning
confidence: 99%